Nimodipine administration routes’ role on Aneurysmal Subarachnoid Hemorrhage outcomes - A retrospective cohort study - Chiomento da Motta, Gabriel; Zortea, Vanelise; Rodrigues Chagas Gonzatti, Janaína; Einsfeld, Lidia (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Aim of the study: To evaluate the role Nimodipine administration route (oral or feeding tube) in the outcome of vasospasm (at 7 and 21 days) in patients hospitalized with aneurysmal subarachnoid hemorrhage (SAH). Methods: The study has a retrospective cohort design, with data collected in a tertiary teaching hospital in Porto Alegre, Brazil. The period analyzed was between January 2019 and January 2023. Patients over 18 years old, diagnosed with SAH and who underwent at least 7 days of hospitalized ni modipine treatment were included. Results: A total of 121 patients were included: 59 received nimodipine orally and 62 via nasoenteral tube. Nimodipine nasoenteral tube use was related to an increase in the regression-adjusted risk of vasospasm in 7 days (RR=2.35; 95% CI: 1.01 - 5.46) and in 21 days (RR=2.40; 95% CI: 1.05 - 5.46). Conclusions: This is the first study in the Brazilian (or even Latin American) context, in which the impact of the nasoenteral route of administration of nimodipine on the outco mes of vasospasm in patients with SAH. The findings suggest that the use of Nimodipine via nasoenteral tube in these patients may be associated with an increased risk of va sospasm outcome, both at 7 and 21 days of treatment. Therefore, the results should be considered in clinical practice for SAH and demonstrate the need for further studies to correlate pharmacokinetics and clinical outcomes.